Experimental and Modeling Analysis of Graphite Electrodes with Various Thicknesses and Porosities for High-Energy-Density Li-Ion Batteries. Issue 7 (1st January 2018) - Malifarge, Simon; Delobel, Bruno; Delacourt, Charles
Abstract : The influence of the negative electrode design on its electrochemical performance with regard to Li insertion/de-insertion is analyzed in this work. A combined experimental/modeling approach is undertaken relying on Newman continuum model. Various designs of industry-grade graphite electrodes (2–6 mAh cm −2 ) were previously characterized by measuring geometric and physical parameters that are used as input parameters in the present model analysis. The half-cell model is successfully validated against rate-capability experiments without any further parameter fitting. The various polarization contributions are then identified based on the model analysis of rate-capability tests on the various electrodes. It emerges that low-loading electrodes suffer from larger particle-scale limitations (mainly solid-diffusion limitation) than high-loading electrodes because of a lower active surface area per geometric area. However, high-loading electrodes undergo large liquid-phase limitations at medium to high current densities: a large overpotential develops because of the formation of a large salt concentration gradient across the cell. Finally, the graphite electrode model is used into a full-cell model vs. LiNi0.33 Mn0.33 Co0.33 O2 (NMC) as the positive electrode. Simulations allow for a forecast of the occurrence of Li plating for various cell designs with the constraint of a constant ratio of negative to positive electrode loading.